Comparative analysis of the organelle genomes of three Rhodiola species provide insights into their structural dynamics and sequence divergences - Xiaolei Yu; Pei Wei; Zhuyifu Chen; Xinzhong Li; Wencai Zhang; Yujiao Yang; Chenlai Liu; Shuqi Zhao; Xiaoyan Li; Xing Liu (BMC Plant Biology, 2023)
Abstract Background Plant organelle genomes are a valuable resource for evolutionary biology research, yet their genome architectures, evolutionary patterns and environmental adaptations are poorly understood in many lineages. Rhodiola species is a type of flora mainly distributed in highland habitats, with high medicinal value. Here, we assembled the organelle genomes of three Rhodiola species (R. wallichiana, R. crenulata and R. sacra) collected from the Qinghai-Tibet plateau (QTP), and compared their genome structure, gene content, structural rearrangements, sequence transfer and sequence evolution rates. Results The results demonstrated the contrasting evolutionary pattern between plastomes and mitogenomes in three Rhodiola species, with the former possessing more conserved genome structure but faster evolutionary rates of sequence, while the latter exhibiting structural diversity but slower rates of sequence evolution. Some lineage-specific features were observed in Rhodiola mitogenomes, including chromosome fission, gene loss and structural rearrangement. Repeat element analysis shows that the repeats occurring between the two chromosomes may mediate the formation of multichromosomal structure in the mitogenomes of Rhodiola, and this multichromosomal structure may have recently formed. The identification of homologous sequences between plastomes and mitogenomes reveals several unidirectional protein-coding gene transfer events from chloroplasts to mitochondria. Moreover, we found that their organelle genomes contained multiple fragments of nuclear transposable elements (TEs) and exhibited different preferences for TEs insertion type. Genome-wide scans of positive selection identified one gene matR from the mitogenome. Since the matR is crucial for plant growth and development, as well as for respiration and stress responses, our findings suggest that matR may participate in the adaptive response of Rhodiola species to environmental stress of QTP. Conclusion The study analyzed the organelle genomes of three Rhodiola species and demonstrated the contrasting evolutionary pattern between plastomes and mitogenomes. Signals of positive selection were detected in the matR gene of Rhodiola mitogenomes, suggesting the potential role of this gene in Rhodiola adaptation to QTP. Together, the study is expected to enrich the genomic resources and provide valuable insights into the structural dynamics and sequence divergences of Rhodiola species.